Rumors of change : essays of five decades - Hassan, Ihab, 1925-2015. (Tuscaloosa, Ala. : University of Alabama Press, 1995)
"These essays span five decades and mirror American culture in the postwar years. They represent Hassan's various topics, styles, critical methods, and social attitudes. From formalism in the forties to multiculturalism in the nineties, from existential engagements to postmodern dubieties, from Paul Bowles, Jean Stafford, and William Burroughs to Peter Matthiessen, Marge Piercey, and Christina Dodwell, the essays move with the momentum of history. But they move critically. In sympathy with their subjects, they challenge nonetheless the cant and pieties of their moment."--Jacket.
pt. 1. Early Appraisals (1954-1963). 1. Paul Bowles: The Pilgrim as Prey. 2. Jean Stafford: The Expense of Style and Scope of Sensibility. 3. William Burroughs: The Subtracting Machine -- pt. 2. Literary Themes and Genres (1959-1984). 4. The Antihero in Modern British and American Fiction. 5. Cities of Mind, Urban Words. 6. Timely Pleasures: Sane and In-Sane -- pt. 3. Perspectives on Postmodernism (1975-1989). 7. Joyce, Beckett, and the Postmodern Imagination. 8. Imagination and Belief: Wallace Stevens and William James. 9. Beyond Postmodernism? Theory, Sense, and Pragmatism -- pt. 4. Criticism and Theory (1989-1994). 10. Fictions of Power: Ideological Discourse in the Humanities. 11. Confessions of a Reluctant Critic or, the Resistance to Literature. 12. Criticism in Our Clime: Parables of American Academe -- pt. 5. Travel, Autobiography, Geopolitics (1988-1994). 13. The Spirit of Quest in Contemporary American Letters. 14. Motion and Mischief: Contemporary British Travel Writing. 15. Japan and the United States: The Burden of Mutual Perception. Envoy: Without Exile: A Postcolonial Intellectual Abroad.
Includes index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: American literature -- 20th century -- History and criticism; English literature -- 20th century -- History and criticism; Littérature américaine -- 20e siècle -- Histoire et critique; Littérature anglaise -- 20e siècle -- Histoire et critique; LITERARY CRITICISM -- American -- General; American literature; English literature; Amerikaans; Letterkunde; American Literature; English; Languages & Literatures; 1900-1999; English literature; United States; Criticism, interpretation, etc